1993
DOI: 10.1007/bf01956159
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of potassium in drinks by pre-treatment with calcium polystyrene sulphonate

Abstract: Dietary potassium intake in patients with chronic renal failure is generally reduced by oral administration of potassium-binding resins. These drugs may cause disturbances of bowel function and have an unpleasant taste. Pre-treatment of drinks with these resins and their subsequent removal may prevent these inconveniences. In four formulas (whole milk, humanised infant formula, apple juice, and orange juice) we were able to lower the potassium content by 50% with calcium polystyrene sulphonate. No important in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…These results were not due to an inactivity of the resin. In fact, when used in beverages such as orange juice and semi-skimmed milk at a concentration in accordance with previous studies (Bunchman et al, 1991;Fassinger et al, 1998), 4% or 6% Kayexalate Õ induced a dramatic potassium content reduction (about 75%) demonstrating, even when used in small quantity, its stronger efficacy than other resins previously described (Schroder et al, 1993). Therefore, compared to the beverage treatments, one may suggest increasing sodium polystyrene sulfonate content into the soaking or boiling water.…”
Section: Discussionsupporting
confidence: 71%
“…These results were not due to an inactivity of the resin. In fact, when used in beverages such as orange juice and semi-skimmed milk at a concentration in accordance with previous studies (Bunchman et al, 1991;Fassinger et al, 1998), 4% or 6% Kayexalate Õ induced a dramatic potassium content reduction (about 75%) demonstrating, even when used in small quantity, its stronger efficacy than other resins previously described (Schroder et al, 1993). Therefore, compared to the beverage treatments, one may suggest increasing sodium polystyrene sulfonate content into the soaking or boiling water.…”
Section: Discussionsupporting
confidence: 71%
“…Currently available sodium and calcium polystyrene sulfonate resins used for the treatment of hyperkalemia are acknowledged to have a gritty texture and unpleasant taste, which can make them difficult for patients to take. 23 , 24 Studies involving other oral medications also show the importance of palatability. Unpleasant taste was associated with poor compliance with therapy in patients receiving antibiotics for the treatment of skin and soft tissue infections, 25 while a survey of elderly patients and their health care professionals showed that compliance with prescribed oral nutritional supplements was low and was affected by taste, texture, and flavor, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason lowering the potassium content of drinks by pre-treatment with calcium polystyrene sulphonate has been suggested [100]. Special care should be taken in patients with end-stage renal failure.…”
Section: Treatmentmentioning
confidence: 99%